2018
DOI: 10.1016/j.celrep.2017.12.075
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role for DsbA in Attacking and Targeted Bacterial Cells during Type VI Secretion System-Mediated Competition

Abstract: SummaryIncorporation of disulfide bonds into proteins can be critical for function or stability. In bacterial cells, the periplasmic enzyme DsbA is responsible for disulfide incorporation into many extra-cytoplasmic proteins. The type VI secretion system (T6SS) is a widely occurring nanomachine that delivers toxic effector proteins directly into rival bacterial cells, playing a key role in inter-bacterial competition. We report that two redundant DsbA proteins are required for virulence and for proper deployme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…To confirm this interaction in the physiologically-relevant context, we generated strains expressing PpkA fused with a C-terminal haemagglutinin (HA) tag (PpkA-HA) and/or RtkS fused with a C-terminal hexahistidine tag (RtkS-His), with the fusion proteins being expressed from the normal chromosomal locations. Strains carrying either or both fusions exhibited normal T6SS-dependent anti-bacterial activity, confirming that the fusions did not impair function ( S7 Fig , [ 32 ]). Using membrane fractions prepared from these strains, specific co-immunoprecipitation of RtkS-His with PpkA-HA, and, conversely, co-purification of PpkA-HA with RtkS-His could be observed ( Fig 7B ).…”
Section: Resultsmentioning
confidence: 62%
“…To confirm this interaction in the physiologically-relevant context, we generated strains expressing PpkA fused with a C-terminal haemagglutinin (HA) tag (PpkA-HA) and/or RtkS fused with a C-terminal hexahistidine tag (RtkS-His), with the fusion proteins being expressed from the normal chromosomal locations. Strains carrying either or both fusions exhibited normal T6SS-dependent anti-bacterial activity, confirming that the fusions did not impair function ( S7 Fig , [ 32 ]). Using membrane fractions prepared from these strains, specific co-immunoprecipitation of RtkS-His with PpkA-HA, and, conversely, co-purification of PpkA-HA with RtkS-His could be observed ( Fig 7B ).…”
Section: Resultsmentioning
confidence: 62%
“…Hijacking a highly conserved and essential molecule of the recipient cell to improve attacker fitness is not uncommon. The examples are CdiA-CT EC93 hijacking essential proteins BamA and AcrB, CdiA-CT EC536 hijacking the recipient CysK, and Ssp2 and Ssp4 hijacking recipient DsbA (Aoki et al, 2008;Diner et al, 2012;Mariano et al, 2018). The ClpP protease, on the other hand, is highly conserved in both prokaryotes and eukaryotic organelles like plastid and mitochondria (Culp and Wright, 2016;Moreno et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the recipient EF-Tu involved in an interbacterial competition of Tse6 remains elusive. A T6SS study in Serratia marcescens demonstrated that the recipient protein DsbA plays a role in activating S. marcescens T6SS effectors Ssp2 and Ssp4, but not Rhs2 (Mariano et al, 2018). The S. marcescens T6SS kills its Ssp2-sensitive siblings only when the recipient cells harbor dsbA homologs (dsbA1 + dsbA2 + ).…”
Section: Introductionmentioning
confidence: 99%
“…The situation seems to be exceptionally complicated in microorganisms possessing complex Dsb system with redundant Dsb proteins. An EcdsbA mutation can be easily complemented in trans, whereas expression from plasmid Serratia marescens dsbA1 (but not dsbA2) or dsbA1, dsbA2 or c8j_1298 of C. jejuni have a deleterious impact on cell growth or results in genetic rearrangements [80].…”
Section: Plos Onementioning
confidence: 99%